2020
DOI: 10.31083/j.jin.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Herbal decoction of Gastrodia, Uncaria, and Curcuma confers neuroprotection against cerebral ischemia in vitro and in vivo

Abstract: Tianma" (Gastrodia) and "gouteng" (Uncaria) are both widely used to treat cerebral ischemia. At the same time, "ezhu" (Curcuma longa) or turmeric, is derived from the dried roots of C. longa.It is a polyphenol known for its anti-inflammatory effects and its promotion of blood vessel endothelial function. This study explored the neuroprotective effects of a water extract of "tianma", "gouteng", and "ezhu" against ischemic injury. Flow cytometry analysis showed that Gastrodia, Uncaria, and Curcuma reduced the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This prescription clears heat, as well as calms the liver, wind and mind. It also confers neuroprotection against cerebral ischemia in vitro and in vivo ( 29 ) and is mainly used to treat headaches, insomnia, and dizziness. A study has shown that adjustment with Tianma Gouteng decoction combined with AEDs in the treatment of epilepsy reduces the frequency and the symptoms of seizures and improves the quality of life of patients who cannot tolerate antiepileptic drugs, such as sodium valproate and CBZ ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This prescription clears heat, as well as calms the liver, wind and mind. It also confers neuroprotection against cerebral ischemia in vitro and in vivo ( 29 ) and is mainly used to treat headaches, insomnia, and dizziness. A study has shown that adjustment with Tianma Gouteng decoction combined with AEDs in the treatment of epilepsy reduces the frequency and the symptoms of seizures and improves the quality of life of patients who cannot tolerate antiepileptic drugs, such as sodium valproate and CBZ ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine has accumulated thousands of years of experience in the treatment of dementia. Modern studies have also shown that many traditional Chinese medicines have neuroprotective effects [45]. In the clinic, TCM has been widely used because of its minor side effects, prolonging the survival time of patients and improving the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Blume in the treatment of ischemic stroke stroke, dementia and other neurodegenerative disease (11,12). In addition, GEB Chinese patent medicine is frequently used in the clinic.…”
Section: Network Pharmacology and Molecular Docking Analysis On Molec...mentioning
confidence: 99%
“…Moreover, GEB has been used as an anticonvulsant in Asian countries for several centuries ( 10 ). Specifically, several classical formulations of GEB have been widely used in clinical practice, such as Tianma Gouteng and Banxia Baizhu Tianma decoction for treating stroke, dementia and other neurodegenerative disease ( 11 , 12 ). In addition, GEB Chinese patent medicine is frequently used in the clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation